Strategi Komunikasi Pemasaran PT Profilia Indoetech Dalam Meningkatkan Penjualan Tangki Air di Tangerang - Siti Megawati Putri; Mochammad Mirza (Brand Communication, 2022)
After explaining the background of the problems that exist in this study with the title Marketing Communication Strategy in increasing Product Sales of PT. Profilia Indotech in Tangerang Pandemic Period. In a study conducted to find out what marketing communication strategies are used to increase sales during the Covid-19 pandemic. And in this study using two theories of Philip Kotler, Terence A Shimp and the type of research used qualitative methods, using the constructivism paradigm, and research results that can be carried out through observation, interviews, and documentation, and using two data sources, namely primary and secondary data. The results of this research that PT. Profilia Indotech to carry out a communication strategy in increasing product sales during the Covid-19 pandemic, namely by selling by distributing brochures, providing discount prices, and also doing door to door. In carrying out a marketing strategy like this to increase sales during the current pandemic